Asuhan Keperawatan Pada Ny.W Dengan Diagnosa Congestive Heart Failure (CHF) Di Ruang Teratai RSUD Waled Kabupaten Cirebon - Arina Tri Noviyani; Ramli Efendi; Adhin Ahmad Fausi; Inka Lestari; Nur Alfi Lail (MEJORA Medical Journal Awatara, 2024)
Congestive Heart Failure (CHF) or heart failure is a condition in which the heart cannot pump blood effectively to meet the body's needs. This study aims to provide an overview of the implementation of Nursing Care for patients with a diagnosis of Congestive Heart Failure (CHF) in the lotus room of Waled Hospital, Cirebon Regency. The method used is a case study approach. The subjects in this case study were one patient with a medical diagnosis of Congestive Heart Failure (CHF) in the inpatient room. The results of the study showed that the management of nursing care in patients with medical diagnosis of Congestive Heart Failure (CHF) in meeting basic needs with Congestive Heart Failure (CHF) nursing problems carried out foot oedema intervention for approximately 10-15 minutes. Swelling in the lower extremity of the patient is reduced or slightly deflated. Based on the results of nursing care carried out on ny.w based on the interventions carried out so that it can be concluded that nebulizer removal can help increase oxygen saturation and foot oedem techniques can reduce swelling in the patient's feet